2018
DOI: 10.1111/bjdp.12272
|View full text |Cite
|
Sign up to set email alerts
|

Anthropomorphism, social understanding, and imaginary companions

Abstract: In two studies, we investigated the correlates of anthropomorphism, the attribution of unobservable mental states to inanimate entities and non-human animals. In Study 1, we investigated the relations between anthropomorphism, social understanding, empathy, prosocial attitudes, and history of childhood imaginary companions in a college sample (N = 264; M age = 19 years, 2 months). In Study 2, we explored the relations between two different measures of anthropomorphism, theory of mind, imaginary companions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 55 publications
(57 reference statements)
1
24
0
Order By: Relevance
“…Upon closer inspection, the literature does not provide a clear picture either. A recent behavioural study found no relationship between measures of dispositional anthropomorphism and direct and indirect measures of Theory-of-Mind in children and adults (Tahiroglu & Taylor, 2019). In the same study, no relationship between situational (e.g., task-based) anthropomorphism and Theoryof-Mind was observed.…”
Section: Main Analysesmentioning
confidence: 73%
See 1 more Smart Citation
“…Upon closer inspection, the literature does not provide a clear picture either. A recent behavioural study found no relationship between measures of dispositional anthropomorphism and direct and indirect measures of Theory-of-Mind in children and adults (Tahiroglu & Taylor, 2019). In the same study, no relationship between situational (e.g., task-based) anthropomorphism and Theoryof-Mind was observed.…”
Section: Main Analysesmentioning
confidence: 73%
“…Anthropomorphising the situation might help us to become more familiar, predict or master a situation, but people that have a higher tendency to anthropomorphise in general do not show a better understanding of a specific situation nor exhibit increased Theory-of-Mind. However, care is warranted in term of how generalisable this finding is, as the evidence on a relationship between situational anthropomorphism and Theory-of-Mind remains mixed at best (Tahiroglu & Taylor, 2019;.…”
Section: Discussionmentioning
confidence: 99%
“…Upon closer inspection, the literature does not provide a clear picture either. A recent behavioural study found no relationship between measures of dispositional anthropomorphism and direct and indirect measures of theory‐of‐mind in children and adults (Tahiroglu & Taylor, 2019 ). In the same study, no clear relationship between situational (e.g., task‐based) anthropomorphism and theory‐of‐mind was observed.…”
Section: Methodsmentioning
confidence: 99%
“…Research shows that both adults and children readily anthropomorphize non-human entities (Severson and Lemm, 2016;Tahiroglu and Taylor, 2018;Waytz et al, 2010a), though several individual difference and situational contexts promote its occurrence. Epley and colleagues (2007) theorized that anthropomorphism is most likely to occur (1) in contexts in which anthropocentric knowledge is current in the mind and relevant to the situation, (2) when people are motivated to interact effectively with nonhumans, and (3) among individuals who, chronically or situationally, lack a sense of social connection to other humans.…”
Section: Anthropomorphism: Concept and Consequencesmentioning
confidence: 99%